2010
DOI: 10.26719/2010.16.11.1137
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in the special care baby unit of the main children's hospital in Tripoli, Libyan Arab Jamahiriya

Abstract: We investigated the prevalence of neonatal deaths in the special care baby unit (SCBU) at the main children's hospital in Tripoli and the factors associated with these deaths. We reviewed the medical records of all neonates who died in our SCBU from 1 January 2003 to 31 December 2005. A total of 1176 neonates were admitted to our SCBU (59.6% males and 40.4% females). Of these, 260 (22.1%) died: 165 males and 95 females. The reasons for admission to SCBU of the neonates who died were: prematurity (43.9%), birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The study found that 63.1% of the deaths occurred during the early neonate phase, the most critical phase. These results support the early safe intervention of KMC to sick newborns [ 33 ]. A WHO report on Libya in 2017 [ 34 ] showed that KMC is practiced in 23.1% facilities.…”
Section: Discussionsupporting
confidence: 78%
“…The study found that 63.1% of the deaths occurred during the early neonate phase, the most critical phase. These results support the early safe intervention of KMC to sick newborns [ 33 ]. A WHO report on Libya in 2017 [ 34 ] showed that KMC is practiced in 23.1% facilities.…”
Section: Discussionsupporting
confidence: 78%
“… (16) Causes of neonatal death were recorded as respiratory distress (79%), sepsis (32%) and stillbirths (38.35%); most deaths were in the first week of life (61.65%). A study in Tripoli during mid-2000 (3) has shown that the associated causes of neonatal death were respiratory distress (40.4%) and infection (18.5%); the majority of deaths (63.1%) occurred during the early neonatal period whereas (30.8%) were during the late neonatal period and (6.2%) during the post-neonatal period. In both of these studies, (2,3) no metabolic disorders were mentioned as possible causes of death in this critical age which might indicate poor facilities for identifying these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of mortality in neonatal intensive care units are prematurity (43.9%), hypoxic ischemic encephalopathy (16.7%), congenital malformations (15.9%), neonatal infections (14.6%) and other reasons (4.6%) (3) . Due to limited diagnostic facilities and lack of experienced pediatricians trained in metabolic diseases, many unexplained deaths have been reported and are likely to have been misdiagnosed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation